A subset of flavaglines inhibits KRAS nanoclustering and activation - Yurugi, Hajime (2021)
The RAS oncogenes are frequently mutated in human cancers and among the three isoforms (KRAS, HRAS and NRAS), KRAS is the most frequently mutated oncogene. Here, we demonstrate that a subset of flavaglines, a class of natural anti-tumour drugs and chemical ligands of prohibitins, inhibit RAS GTP loading and oncogene activation in cells at nanomolar concentrations. Treatment with rocaglamide, the first discovered flavagline, inhibited the nanoclustering of KRAS, but not HRAS and NRAS, at specific phospholipid-enriched plasma membrane domains. We further demonstrate that plasma membrane-associated prohibitins directly interact with KRAS, phosphatidylserine and phosphatidic acid, and these interactions are disrupted by rocaglamide but not by the structurally related flavagline FL1. Depletion of prohibitin-1 phenocopied the rocaglamide-mediated effects on KRAS activation and stability. We also demonstrate that flavaglines inhibit the oncogenic growth of KRAS-mutated cells and that treatment with rocaglamide reduces non-small-cell lung carcinoma (NSCLC) tumour nodules in autochthonous KRAS-driven mouse models without severe side effects. Our data suggest that it will be promising to further develop flavagline derivatives as specific KRAS inhibitors for clinical applications.